E-Commerce success in Malaysia fashion industry: a case study on fashion valet - Ab Llah, Nur Izzah Rahmiah; Rahim, Nurul Amirah; Hussin, Husnayati (UMK, 2018)
E-commerce industry has escalated rapidly in the past few decades as many businesses found the Internet technology has opened up a new and effective channel to reach customers globally and make the company more competitive in today’s challenging environment. There are several e-commerce companies excelling around the world, however only a few homegrown ones became successful and well-known regionally or globally. Despite many studies have been done on these successful e-commerce companies, Malaysian-based ecommerce companies have yet to gain proper analysis and understanding on what contribute to their success. The purpose of this paper is to fill this gap by studying one of the top e-commerce companies in the fashion industry in Malaysia called Fashion Valet. The paper adopts a single case study approach where data was collected from various secondary sources and analyses were done to gain insights on what contribute to the success. Based on the findings, we concluded that several factors interplay in making Fashion Valet successful which include the business model, marketing strategies, website quality as well as entrepreneurial qualities of the founders themselves.